Perilaku belajar dan self regulated learning siswa selama belajar dari rumah pada masa pandemi Covid-19 - Atmoko, Adi; Bariyyah, Khairul; Costa, Augusto Da; Hanafi, Husni; Wahyuni, Eny Tri (Jurnal Konseling dan Pendidikan, 2022)
This study aims to (1) describe student learning behavior and student self-regulated learning while studying from home, (2) analyze the relationship between self-regulated learning and student learning behavior while studying from home. This research is a descriptive correlational survey research. The research subjects were 2,867 junior high school students in Indonesia, Grades 7, 8 and 9 were selected by cluster random sampling. Data was collected online using google form. The research instrument uses a learning behavior scale and a self-regulated learning scale developed by the researcher and the instrument validation process has been carried out. Data were analyzed descriptively and correlationally using the JASP (Jeffrey's Amazing Statistics Program) program. Based on the results of the study (1) 1353 (47%) students have good learning behavior while studying from home and 1387 (48%) students have moderate levels of self-regulated learning while studying from home, (2) There is a correlation between learning behavior and self regulated learning.